Unveiling the ethical void: Bias in reference citations and its academic ramifications - Alicia Mattiazzi; Martin Vila-Petroff (Current Research in Physiology)
Citation bias receives scant attention in discussions of ethics. However, inaccurate citation may lead to significant distortions in scientific understanding. Although ethnical and gender citation disparities have been proposed as critical aspects, there are other contributors to citation distortions, like region-based citation bias, that, although less recognized within the scientific community, are equally important. While the foundations of scientific citation include acknowledging pioneers, giving credit to related work, and providing background reading, other more subjective or even questionable criteria are often used when constructing a reference lists. Here, we discuss the potential causes and ethical concerns of citation bias, emphasizing the role of international- or region-based citation bias as one of the most harmful aspects of this ethical breach. We argue that the international scientific community should be aware of this problem and recognize its consequences, which include hindering the accurate dissemination of science, marginalizing underrepresented voices in academia, and impeding scientific progress. We advocate that scientists should compile their reference lists with the same seriousness and integrity they apply to all other aspects of their research.